Optical and structural properties of neodymium-doped KPO3-MoO3 glasses - Galleani, Gustavo [UNESP]; Santagneli, Silvia H. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Messaddeq, Younes [UNESP]; Maia, Lauro J.Q.; Nunes, Luiz A.O. (Elsevier, 2017)
Glasses of composition (mol%) 75KPO3-(25-x)MoO3-xNd3 +, with 0 ≤ x ≤ 1.0, have been prepared and characterized. Thermal and structural properties of the glasses were studied by Differential Scanning Calorimetry (DSC) and Raman scattering spectroscopy. The thermal stability against crystallization on heating was evaluated. Absorption spectra in the visible and infrared regions were collected and analysed, and photoluminescence excitation and emission spectra were obtained under 804 nm diode laser excitations. Using the Judd-Ofelt formalism, the Ω2, Ω4, and Ω6 parameters and the radiative lifetime (τr) were calculated for the 4F3/2 excited state. A fluorescence quantum efficiency for this level (QE = τf / τr) of 58% was determined for glass with x = 0.6.
Keywords: Lifetime; Nd3 + ions; Optical properties; Phosphate glasses